Adherence to behavioral therapy and psychiatry visits in a safety‐net setting in Virginia, USA. (6th March 2014) - Moczygemba, Leticia R.; Osborn, Robert D.; Lapane, Kate L.
Abstract Little is known about predictors of adherence to outpatient behavioural therapy and psychiatry visits in those who experience homelessness. Yet, consistent receipt of services in the community is critical to preventing use of acute care psychiatric services, which cause a significant cost burden to the mental health system. This retrospective study examined sociodemographic, housing instability and health‐related factors associated with adherence to behavioural therapy and psychiatry appointments among 1711 clients served by an urban healthcare for the homeless centre in Virginia, USA. Clients ≥18 years old with a behavioural health condition who had an intake assessment and at least one behavioural therapy or psychiatry appointment scheduled during October 2005–September 2009 were eligible for the study. Of those with scheduled behavioural therapy visits, 27.7% were high adherers and 19.3% did not attend any appointments, whereas of those with scheduled psychiatry visits, 13.6% were high adherers and 22.1% did not attend any appointments. African Americans, when compared with whites, and those with a primary diagnosis of bipolar disorder were less likely to be high adherers to behavioural therapy. Women and being ≥35 years old were associated with a decreased likelihood of failing to attend psychiatry appointments, whereas African Americans, when compared with whites, and those with co‐occurring disorders were more likely to not attend any psychiatry appointments. Understanding factors related to adherence to behavioural health services can help homeless care providers tailor strategies for improving visit adherence.